THE EFFECT OF ORGANIZATIONAL COMMITMENT, ORGANIZATIONAL CULTURE, AND ORGANIZATIONAL CITIZENSHIP BEHAVIOR (OCB) ON EMPLOYEE PERFORMANCE WITH JOB SATISFACTION AS AN INTERVENING VARIABLE (Study at PT Pegadaian Area of Malang) - Anis Sya’bania; Heri Pratikto; Sopiah Sopiah (International Journal of Economics, Business and Innovation Research, 2023)
The purpose of this study was to examine the effect of organizational commitment, organizational culture, and organizational citizenship behavior (OCB) on employee performance through job satisfaction at PT Pegadaian Malang area employees. This type of research is descriptive and explanatory research, with a quantitative approach. For data processing using SEM-PLS. Questionnaire survey data were collected both online using Google Forms and offline through questionnaires. The sample in this study was 163 employees of PT Pegadaian Malang. The findings show that organizational commitment, OCB, and organizational culture can explain job satisfaction and employee performance. Organizational commitment, organizational culture, and OCB have a positive and significant effect on job satisfaction, organizational commitment, organizational culture, and OCB, job satisfaction has a positive and significant effect on employee performance, and job satisfaction has a positive and significant effect mediating organizational commitment, organizational culture and OCB on performance employee. These results indicate that job satisfaction plays an important role in mediating organizational commitment, OCB, organizational culture, and employee performance at PT Pegadaian Malang area. The findings of this study should be able to attract decision-makers at PT Pegadaian, especially in the Malang area, to pay more attention to maintaining and increasing organizational commitment, OCB, and organizational culture that has employee job satisfaction. The results of this study are also expected to contribute to the development of the science of human resource management and organizational behavior.